The potential of soluble programmed death-ligand 1 (sPD-L1) as a diagnosis marker for colorectal cancer - Shao, Weifang; Xu, Yanhua; Lin, Suzhen; Gao, Junli; Gao, Junshun; Wang, Hong (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is one of the most significant neoplasms with high morbidity and mortality. Activation of the programmed death protein 1/programmed death ligand 1 (PD-1/PD-L1) signaling pathway results in tumor immune evasion by suppressing the activity of T cells. The correlation of soluble PD-L1 (sPD-L1) in serum/plasma with clinicopathological features, lymph node metastasis, diagnosis and prognosis is less clear. The aim of this study was to investigate the relationship between sPD-L1 and diagnosis potential and clinicopathological features and prognosis of CRC patients. Three hundred patients with CRC were included in this study. sPD-L1 was measured by ELISA. Pretreatment levels of sPD-L1 were significantly elevated in CRC patient sera compared to healthy donors (P<0.001). The median value of sPD-L1 in healthy donors, CRC with non-lymph node metastasis, and CRC with lymph node metastasis were 246.78±50.2pg/mL, 284.12±52.7pg/mL, and 321.31±55.3pg/mL, respectively. ROC analysis of sPD-L1 allowed significant differentiation between HC group and CRC group (lymph node metastasis and non lymph node metastasis (AUC=0.861, 95% CI 0.830-0.887, p<0.001). sPD-L1 is a potential biomarker for the diagnosis of CRC. Multivariate analysis showed that lymph node metastasis and tumor differentiation were independent prognostic factors (all P < 0.01), and sPD-L1 was not correlated with the CRC prognosis (p>0.05).